Evaluation of the Factory Implementation of the CIPP Method in Indonesian Vocational Education - Ida Nugroho Saputro; Aryanti Nurhidayati; Suharno Suharno; Chandra Winiawati; Revira Yunika; Mutiara Porista Kusumadevi (AL-ISHLAH: Jurnal Pendidikan, 2023)
Education is a crucial component of human resource development. Education will impact the quality of graduates and serve as a standard for business and industry. However, due to the resulting disparities, education becomes a serious issue, resulting in a high unemployment rate. One of the initiatives to improve the quality of education, particularly vocational education, is the implementation of the teaching factory. This study's objective is to evaluate the implementation of a teaching factory in vocational education, specifically at Vocational High School 2 Klaten for building majors. In this instance, the Directorate of Vocational High School Development evaluates the implementation of the teaching factory in the fields of expertise Building Modeling and Information Design (DPIB) and Building Concentration, Sanitation, and Maintenance (KGSP). In this study, context, input, process, and product (CIPP) were examined using a quantitative methodology known as purposeful sampling. According to the findings, the implementation of a teaching factory in vocational education remains insufficient due to a number of constraints, including a lack of human resources, infrastructure, and industry collaboration.